US Programs Affecting Food and Agricultural Marketing - Armbruster, Walter J.; Armbruster, Walter J.; Knutson, Ronald D.; Knutson, Ronald D. (Natural Resource Management and Policy, 2013)
With increasing globalization of markets, a wider array of programs has come to affect the food and agricultural marketing system, and many of today’s programs are more consumer oriented than producer oriented. This book brings together the thinking of the best researchers addressing the topics involved in these programs, and provides readily understood analyses of the challenges and opportunities facing the food and agricultural industry and the programs which impact industry performance. Many public sector programs and institutions affecting food and agricultural marketing were designed in the early and mid- 1900s, and while they have been updated, new demands are constantly being placed on them. The authors discuss the increased scope, complexity, and globalization of markets, the changes in technology that brought these changes about, and the need for policy and program adjustments. They also discuss the development of supply chains domestically and globally, from farm to consumption. The book addresses the safety of the food supply from both domestic and international sources. and the need to assure security of the food supply from external events while maintaining trade and open markets. The breadth of programs treated makes this book valuable to students and scholars in agricultural economics and agribusiness management, as well as to practitioners and policy-makers in the field.